Barriers to vaccination in immunocompromised children: A needs assessment in children with childhood-onset SLE and inflammatory bowel disease - Lloyd, Audrey R.; Ardura, Monica I.; Wise, Kelly; Chavarin, Daniel J.; Boyle, Brendan; Sivaraman, Vidya (Frontiers in Pediatrics, 2023)
Background Vaccination of immunocompromised children (ICC) remains suboptimal. Methods Needs assessment surveys were administered to patients and caregivers during routine ambulatory visits to the rheumatology and gastroenterology clinics at Nationwide Children's Hospital (NCH) from January 1 through August 31, 2018, and to community primary care physicians (PCPs) at their monthly meeting and electronically. Results Completed surveys were received for 57 patients (31 with childhood-onset systemic lupus erythematosus (c-SLE) and 26 with inflammatory bowel disease (IBD)) and 30 PCPs. Of the patient cohort, 93% (n = 53) felt their PCP was well informed about vaccines and 84% (n = 47) received vaccinations from either their PCP or local health department. Two patient surveys noted concerns of vaccine safety. Among the 30 responses completed by PCPs 50% (n = 15) preferred to provide all vaccines themselves, however, only 40% (n = 12) of PCPs felt “very confident” when providing vaccines to ICC. Further, 83% (n = 25) did not stock the 23-valent pneumococcal vaccine and only 27% (n = 8) routinely recommended vaccination of household contacts. Conclusions Our study found a discordance between parent and PCP comfort in vaccinating ICC, highlighting an important barrier to vaccination in this patient population. In our cohort of patients, vaccine hesitancy was not a barrier to vaccination.